Measuring the importance of road segments using shortest path counting problem - Gozun, Brian C. (Animo Repository, 2009)
This study applied the shortest path counting problem (SPCP) in measuring the degree of importance of road segments which is attributed to the number of times a road segment is included in the shortest path. The road segments most frequently used represent the links that are commonly used when moving from one origin to destination. The method is applied to the Manila road network and the results correspond to the highly congested networks in Manila. Knowing which road networks are congested is beneficial for managers so that they can plan their routes with more efficiency.